(untitled) (American Journal of Islam and Society, 1994)
Background of South African Islam In 1994, South Africans will celebrate three centuries of Islam in South Africa. Credit for establishing Islam in South Africa is usually given to Sheikh Yusuf, a Macasser prince who was exiled to South Africa for leading the resistance against the Dutch colonization of Malaysia. The fitst Muslims in South Africa, however, were actually slaves who had been imported, beginning in 1677, mainly from India, the Indonesian archipelago, Malaysia, and Sri Lanka, by the Dutch colonists living in the Cape. The Cape Muslim community, popularly but inaccurately known as "Malays" and known under apattheid as "Coloreds," is the oldest Muslim community in South Africa. The other major Muslim community was established over a century later by indentured laborers and tradespeople from northern India, a minority of whom weae Muslims. The majority of South African Indian Muslims, classified as "Asians" or "Asiatics," now live in Natal and Tramvaal. The third ethnically identifiable group, classified as "Aftican" or "Black," consists mainly of converts or their descendants. Of the entire South African Muslim population, roughly 49 percent are "Coloreds," nearly 47 pement are "Asians," and, although statistics regarding "Africans" ate generally unreliable, it is estimated that they are less than 4 percent. Less than 1 percent is "White." Contributions to South African Society Although Muslims make up less that 2 petcent of the total population, their presence is highly visible. There ate over twenty-five mosques in Cape Town and over one hundred in Johannesburg, making minarets as familiar as church towers Many are histotic and/or architectuml monuments. More importantly, Muslims ate uniquely involved in the nation’s cultwe and economy. The oldest extant Afrikaans-language manuscripts are in the Arabic script, for they ate the work of Muslim slaves writing in the Dutch patois. South African historian Achrnat Davids has traced many linguistic elements of Afrikaans, both in vocabulary and grammar, to the influence of the Cape Muslims. Economically, the Indian Muslims axe the most affluent, owing primarily to the cirmmstances under which they came to South Africa. Muslim names on businesses and buildings are a familiar sight in all major cities and on those UniveAty campuses that non-Whites were allowed to attend during apartheid ...